Antibacterial activity of Bacterocin producing Lactobacillus sp., isolated from traditional milk products - P.K. Sivakumar, A. Arokiyamary and (Current Botany, 2011)
<span style="font-size: 8pt; font-family: Byington; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-family: 'Times New Roman';">Lactic acid bacteria commonly used as a natural food preservative to improve the food safety and stability. These organisms produce certain antimicrobial substance such as bacteriocins. The present study was focused on isolation and characterization of bacteriocin producing Lactobacillus sp., from a traditional milk product such as Curd, Cheese, Butter, Milkpeda and Ghee. The isolates were identified, based on characteristics of the strains of Lactobacillus sp., as present in Bergey’s manual of determinative bacteriology, the metabolite bacteriocin was extracted from the isolated Lactobacillus LBC and the antibacterial activity was evaluated against bacterial pathogens. The bacteriocin producing Lactobacillus LBC exhibited the highest zone of inhibition (15 mm) against Staphylococcus aureus. This study revealed the possibility of using bacteriocin as food biopreservative to control food spoilage and pathogenic bacteria.